Pengaruh Kemandirian Belajar Peserta Didik Terhadap Hasil Belajar Matematika Pada Materi Bangun Datar - Rahmanita Nurul Aulia; Nedin Badruzzaman; Nurlinda Safitri (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine the effect of student learning independence on mathematics learning outcomes in flat shape material for fourth grade students of SD Negeri Leuwiliang 04. The type of research is quantitative research, the type used is causal research, while the population in the study is all class students IV Leuwiliang 04 Public Elementary School for the 2021/2022 academic year with a total of 81 students who are also the research sample. Based on the calculation tcount of 32.05 is greater than the ttable of 2.021. Because tcount (32.05) > ttable (2.021) then Ho is rejected and Ha is accepted. In addition, it is evidenced by a correlation coefficient of 0.98 with a determination coefficient of 96.04%, the results of data processing and discussion can be concluded that there is a significant positive influence between student learning independence on mathematics learning outcomes in flat shape material. In other words, the greater the level of student learning independence, the higher the mathematics learning outcomes obtained by class IV students at SD Negeri Leuwiliang 04.